2019
DOI: 10.3390/su12010104
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Social Welfare Effect of Environmental Regulation Policy Based on a Market Structure Perspective and Consumer

Abstract: With the implementation of regulatory policies, some new problems are emerging, such as uneven governance effects, large differences in economic growth, and social welfare inequalities. In order to promote the sustainable development of both the economy and the environment, it is necessary to provide theoretical explanations for the above phenomena. Thus, this paper constructs a theoretical model of social welfare effects based on the Cournot model. Additionally, the scenario analysis method is used to analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…However, it is worth noting that only the wealth of countries does not determine the higher priority of environmental issues in the respective societies. Moreover, studies show that the "Environmental Kuznets Curve" (EKC) (according IOP Publishing doi:10.1088/1755-1315/1269/1/012026 3 to which environmental damage increases at the initial stage of economic development, however, this damage decreases in economically rich countries) is not confirmed in practice [9], [10]. Studies have shown that the level of public education in countries is related to the right perception of environmental issues [8].…”
Section: Theory/calculationmentioning
confidence: 99%
“…However, it is worth noting that only the wealth of countries does not determine the higher priority of environmental issues in the respective societies. Moreover, studies show that the "Environmental Kuznets Curve" (EKC) (according IOP Publishing doi:10.1088/1755-1315/1269/1/012026 3 to which environmental damage increases at the initial stage of economic development, however, this damage decreases in economically rich countries) is not confirmed in practice [9], [10]. Studies have shown that the level of public education in countries is related to the right perception of environmental issues [8].…”
Section: Theory/calculationmentioning
confidence: 99%
“…In the face of environmental regulations, heavily polluting enterprises in free competitive markets could increase their technology investment and develop cleaner products to maintain market competitiveness [66]. Therefore, the impact of NEPL on enterprises' market competitiveness differs under different competitive market structures [67]. In this study, the Herfindahl index is used to measure the degree of market competition.…”
Section: Market Structure Differences Analysismentioning
confidence: 99%
“…The literature [14] argues that VR technology combined with news reporting produces VR news with the characteristics of "reproduction" and "restoration" of news events compared with traditional new media communication technology, which can promote the development of the new media industry. The research [15] focuses on the impact of ancient resources on environmental visual design and conducts experiments with object-shaped symbols. Using ancient resources in urban architectural environments can benefit the development of the environmental visual design industry, as shown by the results.…”
Section: Introductionmentioning
confidence: 99%